2021
DOI: 10.1159/000510589
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Operative Treatment of Symptomatic Urolithiasis in Germany

Abstract: <b><i>Purpose:</i></b> The guidelines of the German, European, and American Urological Associations on urolithiasis advise against general ureteral stenting before and after an uncomplicated ureterorenoscopy (URS). However, German and European guidelines state that stenting prior to URS facilitates stone extraction and reduces intraoperative complications. According to the published literature, German practice seems to deviate from recommendations. This nationwide survey aimed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In summary, 87% of urological departments stated that less than 30% of all urinary stones are treated with SWL. 43% of all departments stated that 51–70% of all stone therapy is done via ureterorenoscopy (URS) and further 43% of all departments stated that more than 70% of all cases are managed via URS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, 87% of urological departments stated that less than 30% of all urinary stones are treated with SWL. 43% of all departments stated that 51–70% of all stone therapy is done via ureterorenoscopy (URS) and further 43% of all departments stated that more than 70% of all cases are managed via URS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…American, European and German guidelines state that routine stenting after URS and stone removal is not necessary. Despite the downsides of stenting, data from America and Germany indicate that urologists are reluctant to omit stenting [ 7 , 8 ]. This hesitancy might be based on a higher risk of readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group’s empirical study showed that after primary URS, German urological departments insert a DJ in 79.6% of cases, a Mono-J (MJ) in 7.3% and only 3.6% prefer tubeless procedure. After secondary URS, departments insert a DJ in 62.2% of procedures, a MJ in 10.5% and omit stenting in 14.0% [ 7 ]. Mittakanti published an observational study including 17,129 patients from North America in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…A survey among German urological departments showed that after primary URS, 79.6% of urologists inserted a DJ, 7.3% inserted a MJ, and 3.6% omitted a stent. After secondary URS, urologists inserted a DJ in 62.2% of cases, a MJ in 10.5% and did not insert a stent in 14.0% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, treatment modalities (high rate of pre-stenting) deviate in a highly developed country with a well-equipped health system like Germany, and this could be due to financial incentives and a missing endourological department system [ 16 ].…”
Section: Discussionmentioning
confidence: 99%